How "Indians" Think Colonial Indigenous Intellectuals and the Question of Critical Race Theory - Lamana, Gonzalo (University of Arizona Press, 2019)
The conquest and colonization of the Americas marked the beginning of a social, economic, and cultural change of global scale. Most of what we know about how colonial actors understood and theorized this complex historical transformation comes from Spanish sources. This makes the few texts penned by Indigenous intellectuals in colonial times so important: they allow us to see how some of those who inhabited the colonial world in a disadvantaged position thought and felt about it. This book shines light on Indigenous perspectives through a novel interpretation of the works of the two most important Amerindian intellectuals in the Andes, Felipe Guaman Poma de Ayala and Garcilaso de la Vega, el Inca. Building on but also departing from the predominant scholarly position that views Indigenous-Spanish relations as the clash of two distinct cultures, Gonzalo Lamana argues that Guaman Poma and Garcilaso were the first Indigenous activist intellectuals and that they developed post-racial imaginaries four hundred years ago. Their texts not only highlighted Native peoples' achievements, denounced injustice, and demanded colonial reform, but they also exposed the emerging Spanish thinking and feeling on race that was at the core of colonial forms of discrimination. These authors aimed to alter the way colonial actors saw each other and, as a result, to change the world in which they lived.